Formation of an innovative model for the development of e-commerce as part of ensuring business economic security - Alazzam, Farouq Ahmad Faleh; Tubishat, Bassam Mustafa Abdel-Rahman; Savchenko, Olena; Pitel, Nataliia; Diuk, Oksana (Business: Theory and Practice, 2023)
The purpose of the article is to formulate a methodological approach to building a model of e-commerce development in the context of ensuring the economic security of business. The object of the study is the business activity of socio-economic systems and their economic security. The scientific task is to model the stages and processes of e-commerce development in the framework of ensuring business economic security. The key problem is the lack of a clear methodological approach to modeling the development of e-commerce in the context of ensuring the economic security of business. A review of the literature showed that there is no single approach to solving this problem. The research methodology involves the use of functional modeling technology. This is achieved through a graphical modeling method. Based on the results of the study, the main model for the development of e-commerce in the framework of ensuring the economic security of business was presented. Each block has been modeled separately for better understanding. The scientific innovativeness of the presented research results consists in the presented methodological approach to determining the ways for the development of e-commerce in the framework of ensuring the economic security of a business.